2014
DOI: 10.1007/s00432-014-1854-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinicopathological significance of EED, SUZ12 and EZH2 mRNA in colorectal cancer

Abstract: High expression of EED, SUZ12 and EZH2 might contribute to the CRC development/progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 47 publications
5
57
0
13
Order By: Relevance
“…EZH2 is a transcription inhibition factor that inhibits the transcription of multiple cancer suppressor genes and gives rise to the enhancement of invasion and metastasis; it breaks the balance between the promotion and the inhibition of associated genes by migration, which results in the invasion and metastasis of tumors (22). Abnormally high expression of EZH2 may promote cell proliferation: EZH2 gene expression is markedly increased in multiple tumor types including in the prostate, breast, kidney and lung (8). Therefore, it can be concluded that EZH2 is an oncogene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EZH2 is a transcription inhibition factor that inhibits the transcription of multiple cancer suppressor genes and gives rise to the enhancement of invasion and metastasis; it breaks the balance between the promotion and the inhibition of associated genes by migration, which results in the invasion and metastasis of tumors (22). Abnormally high expression of EZH2 may promote cell proliferation: EZH2 gene expression is markedly increased in multiple tumor types including in the prostate, breast, kidney and lung (8). Therefore, it can be concluded that EZH2 is an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the EZH2 gene participated in cellular growth regulation (6,7). The mechanism underlying the function of EZH2 function was the inhibition of the Wnt signaling pathway in chromatin and the promotion of cell proliferation (7,8). Furthermore, as a transcription inhibition factor, EZH2 influenced the activity of multiple genes at the gene level; most notably, it inhibited tumor metastasis genes (including phosphoinositide, protein kinase B and matrix metalloproteinases), aiding the promotion of infiltration and migration of cancer cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of EZH2 mRNA expression based on a resource of tissue samples with follow-up data have provided invaluable information about clinical outcome of cancer patients. [39][40][41] In this study, urinary cf-EZH2 mRNA levels were found to be associated with multifocality and stage of MIBC patients. Based on the optimal cutoff value of cf-EZH2 mRNA that distinguishing the two types of BC, we divided the MIBC patients into two groups, with high and low EZH2 expression.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies of EZH2 mRNA expression based on a resource of tissue samples with follow‐up data have provided invaluable information about clinical outcome of cancer patients . In this study, urinary cf‐EZH2 mRNA levels were found to be associated with multifocality and stage of MIBC patients.…”
Section: Discussionmentioning
confidence: 60%
“…In mammals, there are two types of polycomb group complexes, PCR1 and PCR2. The PCR2 complex consists of four core components: Ezh2, Suppressor of Zeta 12 (SUZ12), EED, and retinoblastoma associated protein 46/48 [ 13 ]. Ezh2 with SET domain forms a complex, which catalyzes H3K27me3 and is involved in the silencing of tumor suppressor genes such as Disabled homology2-interaction protein (DAB2IP) (Fig.…”
Section: Role Of Ezh2 In Prostate Cancermentioning
confidence: 99%